Implementasi Quality Control (QC) Penggunaaan Alat Point Of Care Testing (POCT) sebagai Upaya Jaminan Mutu Hasil Pemeriksaan di Puskesmas Cempaka Kota Banjarmasin - Yuliana Salman; Muhammad Ilham Farihi; Yudi Yahya (HB PRESS, 2023)
Clinical Laboratory is a health laboratory that carries out clinical specimen examination to obtain information about individual health, especially to support diagnose disease, and restore health, therefore quality control (QC) must be applied, especially in utilization of POCT tools. This research approach uses a qualitative approach with data collection methods through interviews, observation and documentation. The object of this research was the Cempaka Public Health Center based on recommendations and permits from the Banjarmasin City Health Office with the research respondents being the Head of the Clinical Laboratory, the Laboratory Quality Assurance Team and the Laboratory Assistant. The variable of this research was the implementation of QC using the POCT tools tool at the pre-analytical, analytical and post-analytic stages. Based on the results of interviews, observations and documentation, data was obtained that the Head of the Puskesmas formed an Internal Audit Team to carry out monitoring and evaluation every 6 months, but the last activity was carried out in 2019. Aspects audited in Monitoring Evaluation Indicators of the clinical is about SOP (Standard Operational Procedure) for the implementation of examinations in the laboratory using the FMEA (Failure, Mode, Effect Analysis) method. The implementation of Quality Control in the pre-analytical, analytical and post-analytic stages is in accordance with the applicable policies and SOPs. Monitoring and Evaluation of Clinical Quality Indicators should be carried out regularly and continuously so that the results of the examination obtained are guaranteed quality and can be used for determining the right diagnosis.